2020
DOI: 10.3390/antiox9030263
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Doxorubicin-Induced Autophagy Attenuates Oxidative Stress and Skeletal Muscle Dysfunction

Abstract: Clinical use of the chemotherapeutic doxorubicin (DOX) promotes skeletal muscle atrophy and weakness, adversely affecting patient mobility and strength. Although the mechanisms responsible for DOX-induced skeletal muscle dysfunction remain unclear, studies implicate the significant production of reactive oxygen species (ROS) in this pathology. Supraphysiological ROS levels can enhance protein degradation via autophagy, and it is established that DOX upregulates autophagic signaling in skeletal muscle. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…However, it is also hypothesized that DOX can directly stimulate autophagy, which in turn can jeopardize the cellular defenses against ROS production [12]. Evidence of this has been shown in skeletal muscle where prevention of DOX-induced autophagy in the soleus was associated with enhanced transcription of antioxidant response element-related genes and increased antioxidant capacity [39]. These beneficial modifications to muscle redox balance resulted in the attenuation of mitochondrial dysfunction and ROS emission [39].…”
Section: Relationship Between Autophagy and Oxidative Stressmentioning
confidence: 99%
“…However, it is also hypothesized that DOX can directly stimulate autophagy, which in turn can jeopardize the cellular defenses against ROS production [12]. Evidence of this has been shown in skeletal muscle where prevention of DOX-induced autophagy in the soleus was associated with enhanced transcription of antioxidant response element-related genes and increased antioxidant capacity [39]. These beneficial modifications to muscle redox balance resulted in the attenuation of mitochondrial dysfunction and ROS emission [39].…”
Section: Relationship Between Autophagy and Oxidative Stressmentioning
confidence: 99%
“…Subsequent studies have corroborated this evidence and demonstrated atrophy and contractile dysfunction within both fast-and slow-twitch muscles [1]. While evidence in both male [43,70] and female [71,72] models of DOX myotoxicity demonstrates skeletal muscle atrophy and dysfunction, to date, no study has directly evaluated differences between the sexes when standardized for age, dose of DOX, and rodent strain. Meta-analysis of preclinical studies focused on the effects of DOX on skeletal muscle found male bias within the literature, as the predominance of studies have been conducted in male rodents [73].…”
Section: Sex-related Differences In the Development Of Skeletal Musclmentioning
confidence: 96%
“…However, increased vulnerability to DOX-induced cardiomyopathy in male rodents is associated with mitochondrial lesions and aberrant changes in oxidative stress gene expression, suggesting that cardiac redox imbalance may be more severe in males compared to females [44,45,[93][94][95]. In skeletal muscle, findings across studies suggest that both sexes demonstrate increased skeletal muscle oxidative stress and impaired mitochondrial respiration in response to DOX treatment [6,7,41,42,71,96,97]. Whether there are sex differences in the degree of this DOX-induced increase in oxidants and compromised respiration in skeletal muscle remains to be tested in studies designed specifically for that purpose.…”
Section: Sex Differences In Redox Abnormalities and Mitochondrial Resmentioning
confidence: 99%
“…As a result, ROS are produced, in particular superoxide anion radicals, via the reduction of DOX’s quinone moiety to an unstable semiquinone [ 54 ]. This redox cycling significantly elevates skeletal muscle hydrogen peroxide (H 2 O 2 ) emission without perturbing homeostatic antioxidant buffering capacity [ 55 , 56 , 57 ] and alters bioenergetic efficiency by impinging on the functionality of respiratory complexes, leading to modifications that promote oxidative damage (e.g., lipid peroxidation) [ 56 , 58 ]. Recent findings from the Hulmi group suggest that DOX-induced skeletal muscle perturbations are predominately influenced by enhanced transcription of REDD1 as part of the transcriptional program regulated by oxidative stress sensitive tumour suppressor protein, p53, a master regulator of cellular homeostasis [ 59 , 60 , 61 ].…”
Section: Mechanisms Of Chemotherapy-induced Cachectic Myopathymentioning
confidence: 99%
“…One such pathway was the activation of the endoplasmic reticulum stress/unfolded protein response signalling cascade, which can negatively regulate protein synthesis [ 67 ]. However, there were divergent responses between different types of striated muscle (i.e., heart, diaphragm, and limb skeletal muscles) and the expression of markers involved in this signalling cascade, elicited by DOX [ 55 , 68 ]. Thus, further research is required to enrich the understanding of the processes regulating the skeletal muscle protein balance during DOX treatment.…”
Section: Mechanisms Of Chemotherapy-induced Cachectic Myopathymentioning
confidence: 99%